Technical success, clinical efficacy, and insight into the causes of restenosis after the percutaneous coronary intervention of de novo coronary artery lesions using a paclitaxel-coated balloon with citrate ester excipient - Tervo, Jerry; Kärkkäinen, Jussi M.; Rissanen, Tuomas T. (Frontiers in Cardiovascular Medicine, 2022)
Objectives The aim of this all-comers registry study was to investigate the technical success, clinical efficacy, and safety of a drug-coated balloon (DCB) with paclitaxel combined with citrate ester excipient (CEE) in percutaneous coronary intervention (PCI) of de novo coronary lesions in an all-comers population. Materials and methods A total of 338 consecutive PCIs using the DCB (CEE)-only approach comprising 406 de novo lesions were included in the study. Technical success was determined by the successful delivery of the device and no need for bailout stenting. Results The mean follow-up time was 25 ± 12 months. The mean age of patients was 71 ± 11 years, and 48% had the acute coronary syndrome. A total of 55% of the patients were at risk of factor bleeding. The delivery of DCB was successful in 98% of cases. The overall technical success rate was 83%. Bailout stenting was used in 9% of lesions. Rotational atherectomy was used in 11% of cases before the DCB-only approach. The mean diameter of the DCBs used was 2.7 ± 0.5 mm and 38% of DCBs were large (≥3.0 mm). The 12-month MACE rates were 5.4 ± 1.7 and 18.3 ± 3.1% in stable CAD and in ACS, respectively. The respective target lesion revascularization (TLR) rates were 3.0 ± 1.3 and 8.5 ± 2.3%. Unacceptable acute recoil (>30%) was found in 74% of cases that needed repeat revascularization. No acute vessel closures occurred after DCB treatment. Conclusion The DCB-only strategy using a paclitaxel-coated (CEE) device was technically feasible, safe, and effective in an all-comers population. Acute recoil was found as a significant cause of restenosis after the DCB-only strategy.